Frequency of Hypothyroidism in Βeta Thalassemia Patients - Javeid iqbal, Khurshid A. Khan, Zohaib A Khan, Sadia Salman, Amna Riaz, Sadia Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the frequency of thyroid hypo-functioning in β-thalassemia patients presenting at Endocrinology Outpatient Department of Jinnah Hospital, Lahore. Study design: Cross-sectional descriptive study Place and duration of study: Allama Iqbal Institute of Diabetes and Endocrinology, Jinnah Hospital Lahore from 5th June 2019 to 4th January 2020 Methodology: One hundred diagnosed cases of β-thalassemia of both genders with age range of 5-19 years were included. Random blood samples were taken to measure serum thyroid stimulating hormone (TSH) and free T4 levels by Enzyme Linked Immunosorbent Assay (ELISA). Results: Hypothyroidism was present in 32 (32%) patients. The frequency of hypothyroidism was same in 5-9 years versus 10-19 years age groups with no significant gender differences (p 0.434). The mean levels of ferritin were 5102±1134 ng/ml in thyroidhypo-functioning cases was 3687±1425 ng/ml in normal-functioning thyroid patients (P 0.001). Conclusion: Hypothyroidism is highly prevalent in β-thalassemia patients. Periodic check-ups are recommended for early diagnosis and interceptive treatment.